The Influence of Human Resource Practices on Job Satisfaction: A Study Among Employees of an Enforcement Agency - Amutha, Mohan (2011)
The purpose of this study is to investigate the relationship between human resource management ( HRM ) practices in enforcement agencies employees related to their job satisfaction. First of all, the study will concentrate on factors such as performance management system, training and development and compensation and benefits in relation with job satisfaction in the enforcement agency. The aims of this study is to identify whether this three factors such as performance management system, training and development and compensation and benefits were positively correlated with employees' job satisfaction. The respondents of the study is consist of the 120 employees from Royal Malaysia Customs of Perlis. The result from the research done revealed that three component measure of human resource practices is valid. It is found that there was a significant relationship between human resource practices toward employees' job satisfaction. This is confirming that performance management system, training and development and compensation and benefits is very important to influence employees' job satisfaction. When the employees satisfied with their jobs, the contribution given by the them can ensure the organization's goals achieved as whole.